2013
DOI: 10.1309/ajcp9zagkvj8pdax
|View full text |Cite
|
Sign up to set email alerts
|

Needle-Core Biopsy in the Pathologic Diagnosis of Malignant Lymphoma Showing High Reproducibility Among Pathologists

Abstract: Needle-core biopsy is an effective technique for the diagnosis of lymphoma and should be considered the first-line procedure for cases with suspicion for lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 23 publications
3
64
0
3
Order By: Relevance
“…24 In certain disease subtypes, for instance, diffuse large B-cell lymphoma, the diagnostic yield of CNB is high because the distribution of lymphomatous cells is fairly uniform (our results demonstrated 96.8% of USCB were fully diagnostic). Tissue architecture is more difficult to assess in lesions which are only patchily affected by disease, or where diagnostic cells are sparse or unevenly distributed.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…24 In certain disease subtypes, for instance, diffuse large B-cell lymphoma, the diagnostic yield of CNB is high because the distribution of lymphomatous cells is fairly uniform (our results demonstrated 96.8% of USCB were fully diagnostic). Tissue architecture is more difficult to assess in lesions which are only patchily affected by disease, or where diagnostic cells are sparse or unevenly distributed.…”
Section: Discussionmentioning
confidence: 57%
“…Tissue architecture is more difficult to assess in lesions which are only patchily affected by disease, or where diagnostic cells are sparse or unevenly distributed. 24 This consideration is particularly relevant in the diagnosis of HD, which is dependent on the identification of Reed-Sternberg cells. These can be scanty within an affected lesion, thus a small specimen can be mis-diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al reported that the core needle biopsy with guidance of ultrasonography have 85 to 87% accuracy for diagnosis of lymphoma (15). After the core needle biopsy and choosing the right lymph node, we performed a second excisional biopsy which yielded the diagnosis of DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…Fine-needle aspiration cytology (FNAC) can be a good first-line method for investigating the cases of cervical lymphadenopathy; it can distinguish reactive lymphoid hyperplasia from malignant lymphoma, is a reliable and cost-effective diagnostic procedure when compared with the gold standard (excisional biopsy)9 and can yield a very good performance. However, as pointed out by Kapoor et al ,10 the role of fine-needle aspiration procedures appears to be limited in making the histological diagnosis of Kimura disease, due to occasional wrong diagnoses through misinterpretation.…”
Section: Discussionmentioning
confidence: 99%